Factors influencing pregnant women’s willingness for HIV testing in North Aceh - Irnanda Aida; Oktalia Sabrida; Erlina Erlina; Myrna Lestari AB; Elvieta Elvieta (Journal of Midwifery and Nursing, 2026)
HIV remains a serious public health concern in Indonesia, particularly among pregnant women who are at risk of transmitting the virus to their infants. Despite the availability of testing, many women are still unwilling to undergo HIV screening. This study aimed to identify factors influencing the willingness of pregnant women to take HIV tests at UPTD Puskesmas Nisam, North Aceh District. A cross-sectional design was employed with 58 pregnant women attending antenatal care in 2025, selected through purposive sampling. Independent variables included knowledge, attitude, husband’s support, and health worker support, while the dependent variable was the willingness to undergo HIV testing. Data were collected using structured questionnaires and analyzed using the Chi-square test. The results showed that most respondents had poor knowledge (67.2%), negative attitudes (65.5%), low husband’s support (67.2%), and inadequate health worker support (69.0%). More than three-quarters (77.6%) of respondents were unwilling to undergo HIV testing. Significant associations were found between knowledge (p=0.012), attitude (p=0.000), husband’s support (p=0.001), and health worker support (p=0.010) with willingness to undergo HIV testing. Conclusion: Knowledge, attitude, husband’s support, and health worker support significantly affect the willingness of pregnant women to undergo HIV testing. Strengthening health education and counseling is essential to increase testing uptake and prevent mother-to-child HIV transmission. Policymakers should integrate HIV testing promotion into antenatal care programs, while health workers are encouraged to implement community-based counseling and spousal involvement initiatives to enhance testing participation.